2019
DOI: 10.1007/s00198-019-04870-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone microarchitecture and bone turnover in hepatic cirrhosis

Abstract: Summary Liver cirrhosis leads to bone loss. To date, information on bone quality (three-dimensional microarchitecture) and, thus, bone strength is scarce. We observed decreased bone quality at both assessed sites, independent of disease severity. Therefore, all patients should undergo early-stage screening for osteoporosis. Introduction Recent studies found low bone mineral density in cirrhosis, but data on bone microstructure are scarce. This study assessed weight-bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 36 publications
(49 reference statements)
3
35
0
1
Order By: Relevance
“…Even though some studies indicated that the etiology of LC could be an important etiopathogenetic factor in bone turnover imbalance (Beck et al, 2018; Jeong & Kim, 2019), other studies claimed the opposite. For instance, a recently published microstructural analysis of tibia and radius did not reveal any significant differences among LC of various etiology (viral, autoimmune, alcoholic, and hemochromatosis‐induced LC) (Wakolbinger et al, 2019), which is in line with our findings of lumbar vertebrae. Additionally, the same group did not observe differences in bone biomarkers, bone microstructure, and BMD between patients with alcoholic and non‐alcoholic CLD (Wakolbinger et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Even though some studies indicated that the etiology of LC could be an important etiopathogenetic factor in bone turnover imbalance (Beck et al, 2018; Jeong & Kim, 2019), other studies claimed the opposite. For instance, a recently published microstructural analysis of tibia and radius did not reveal any significant differences among LC of various etiology (viral, autoimmune, alcoholic, and hemochromatosis‐induced LC) (Wakolbinger et al, 2019), which is in line with our findings of lumbar vertebrae. Additionally, the same group did not observe differences in bone biomarkers, bone microstructure, and BMD between patients with alcoholic and non‐alcoholic CLD (Wakolbinger et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a recently published microstructural analysis of tibia and radius did not reveal any significant differences among LC of various etiology (viral, autoimmune, alcoholic, and hemochromatosis‐induced LC) (Wakolbinger et al, 2019), which is in line with our findings of lumbar vertebrae. Additionally, the same group did not observe differences in bone biomarkers, bone microstructure, and BMD between patients with alcoholic and non‐alcoholic CLD (Wakolbinger et al, 2019). Our findings support the previous observations, suggesting that the ALC‐induced negative effects on bone status originate from CLD rather than alcohol intake per se.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Prethodna histomorfometrijska studija, sprovedena na biopsijama ilijačne kosti pacijenata sa bilijarnom cirozom jetre, pokazala je značajan gubitak trabekularne kosti usled smanjenja debljine i broja trabekula (slika 2) (36), što je potvrđeno i kod pacijenata sa alkoholnom cirozom i hroničnim alkoholnim pankreatitisom (37,38). Slično tome, nedavno publikovana pQCT analiza je pokazala ne samo oštećenje trabekularne već i značajno propadanje kortikalne kosti tibije i radijusa (slika 2) kod bolesnika sa cirozom različitih uzroka, uključujuči alkoholom indukovanu cirozu jetre (39,40). U prilog značajnijem propadanju trabekularne kosti govore i rezultati naše prethodne studije o značajnom smanjenju ukupne koštane mase, broja, debljine i stepena povezanosti trabekula u telima lumbalnih kičmenih pršljenova kod pacijenata sa ACJ (slika 2) (41).…”
Section: Mineralna Gustina Kostiju U Alkoholnoj Cirozi Jetreunclassified